Penerapan Project Based Learning Berbasis Video Animasi untuk Meningkatkan Hasil Belajar Siswa Kelas X pada Materi Struktur Atom - Simamora, Lourdes; Simanjuntak, Hendra; Pane, Eva Pratiwi (PendIPA Journal of Science Education, 2025)
This study aimed to investigate the effect of applying the Project Based Learning (PjBL) model assisted by animated videos on students’ learning outcomes in atomic structure material at Grade X of SMA Negeri 3 Pematangsiantar. The research employed a quasi-experimental design with a pretest-posttest control group. The participants consisted of two classes: the experimental class, which received instruction using PjBL assisted by animated videos, and the control class, which received conventional instruction. The research instrument was a learning achievement test administered before and after the treatment. Data were analyzed using a t-test and N-Gain calculation. The results indicated that the average pretest scores of both classes were relatively the same. After the learning intervention, the average posttest score of the experimental class increased significantly compared to the control class. The average N-Gain score of the experimental class was in the medium/high category, while that of the control class was in the low/medium category. The t-test result showed a significance value of p < 0.05, indicating a significant difference between the two classes. It can be concluded that the implementation of the Project Based Learning model assisted by animated videos has a positive effect on improving students’ learning outcomes in atomic structure material.